Differences in the immunosurveillance pattern associated with DNA mismatch repair status between right‐sided and left‐sided colorectal cancer. Issue 8 (20th July 2020) - Kanno, Hiroki; Miyoshi, Hiroaki; Yoshida, Naohiro; Sudo, Tomoya; Nakashima, Kazutaka; Takeuchi, Mai; Nomura, Yoriko; Seto, Masao; Hisaka, Toru; Tanaka, Hiroyuki; Okuda, Koji; Akagi, Yoshito; et al.
Abstract: Tumor location and immunity play important roles in the progression of colorectal cancer (CRC). This study aimed to investigate the differences in the immunosurveillance pattern between right‐ and left‐sided CRC and analyze their association with clinicopathologic features, including mismatch repair (MMR) status. We included surgically resected stage II/III CRC cases and evaluated the immunohistochemical findings of HLA class I, HLA class II, programmed cell death‐ligand 1 (PD‐L1), PD‐1, CTLA‐4, CD3, CD4, CD8, TIA‐1, T‐bet, GATA3, RORγT, Foxp3, and CD163. A total of 117 patients were included in the analyses; of these, 30 and 87 had right‐ and left‐sided cancer, respectively. Tumor immunity varied according to the tumor location in the overall cohort. Analysis of the tumors excluding those with DNA mismatch repair (MMR) deficiency also revealed that tumor immunity differed according to the tumor location. In right‐sided colon cancer (CC), high expression of Foxp3 ( P  = .0055) and TIA‐1 ( P  = .0396) were associated with significantly better disease‐free survival (DFS). High CD8 ( P  = .0808) and CD3 ( P  = .0863) expression tended to have better DFS. Furthermore, in left‐sided CRC, only high PD‐L1 expression in the stroma ( P  = .0426) was associated with better DFS. In multivariate analysis, high Foxp3 expression in right‐sided CC was an independent prognostic factor for DFS (hazard ratio, 7.6445; 95% confidence interval, 1.2091‐150.35; P  = .0284). In conclusion, the immunosurveillance pattern differs between right‐ and left‐sided CRC, even after adjusting for MMR deficiency. Abstract : Comparison of Kaplan‐Meier curves of disease‐free survival (DFS) in each tumor location excluding DNA mismatch repair deficiency. In right‐sided colon cancer, high Foxp3 ( P  = .0055) and TIA‐1 expression ( P  = .0396) were associated with significantly better DFS. High CD8 ( P  = .0808) and CD3 (0.0863) expression showed a tendency towards better DFS. In left‐sided colorectal cancer, only high sPD‐L1 expression ( P  = .0426) was associated with better DFS.